Engaging older adults in diagnostic safety: implementing a diagnostic communication note sheet in a primary care setting - Alberta Tran; Leah Blackall; Mary A. Hill; Mary A. Hill; William Gallagher (Frontiers in Health Services)
IntroductionAdults over the age of 65 are at a higher risk for diagnostic errors due to a myriad of reasons. In primary care settings, a large contributor of diagnostic errors are breakdowns in information gathering and synthesis throughout the patient-provider encounter. Diagnostic communication interventions, such as the Agency for Healthcare Research and Quality's “Be the Expert on You” note sheet, may require adaptations to address older adults' unique needs.MethodsWe recruited and partnered with older adult patients (n = 6) in focus group sessions to understand their perspectives on diagnostic communication and the existing AHRQ note sheet. A two-page communication and clinic workflow tool was developed and implemented over a 6-month period using three Plan-Do-Check-Act cycles. Physicians, nurses, staff, and patients were surveyed.ResultsMost older adult patients (n = 31) found the tailored diagnostic communication note sheet to be easy-to-use, helpful for provider communication, and would recommend its use to other patients. Physicians and staff members were satisfied with the note sheet and described few challenges in using it in practice.DiscussionOur findings contribute to the growing body of evidence around diagnostic safety interventions and patient engagement by demonstrating the feasibility and benefits of actively involving older adult patients in quality initiatives.